(untitled) (Fiep Bulletin - online, 2011)
Abstract This article brings into context the analysis of how the Law for Encouragement of Sport, asked since 1999 in the city of Ponta Grossa - PR. Aiming to demonstrate that it can become a factor in the search for innovative resources for the sport, whether for sport competition, social or educational. To this end, we attempted to adjust the determinations issued by the Triangle Sábato, regarding the relationship of public service with business and sports institutions. In relation to the determinants for the sport we performed an analysis of legal doctrine emanating from the Brazilian Constitution, culminating Pelé Law with the Law for Encouragement of Sport established in the city of Ponta Grossa - PR. Methodologically this article focuses on the model of a stamp with quantitative research and exploratory, since that analyzes the data contained by the Law for Encouragement of Sport for the years 2000 to 2009. In conclusion there is the achievement of goals, with graphs showing the numbers of projects approved and values and allow for identifying the roles of actors in their inter-relationships used as catalysts for social change.